Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1.X2-2X-4y2-4y
=x2-2x+1-(4y2+4y+1)
=(x+1)2-(2y+1)2
=>(x+1-2y-1)(x+1+2y+1)
=(x-2y)(x+2y+2)
2.x4+2x3-4x-4
=(x2)2-22+2x3-4x
=(x2-2)(x2+2)+2x(x2-2)
=(x2-2)(x2+2+2x)
1) \(2x.\left(x-7\right)-\left(x+3\right)\left(x-2\right)-\left(x+4\right)\left(x-4\right)\)
\(=2x^2-14x-\left(x^2+x-6\right)-\left(x^2-4\right)\)
\(=-15x+10\)
b) \(2x.\left(x+1\right)^2-\left(x-1\right)^3-\left(x-2\right)\left(x^2+2x+4\right)\)
\(=2x.\left(x^2+2x+1\right)-\left(x^3-3x^2+3x-1\right)-\left(x^3-8\right)\)
\(=2x^3+4x^2+2x-x^3+3x^2-3x+1-x^3+8\)
\(=7x^2-x+9\)
c) \(\left(x-5\right)\left(x+5\right)\left(x+2\right)-\left(x+2\right)^3\)
\(=\left(x+2\right).\left[\left(x-5\right)\left(x+5\right)-\left(x+2\right)^2\right]\)
\(=\left(x+2\right).\left(x^2-25-x^2-4x-4\right)\)
\(=\left(x+2\right)\left(-4x-29\right)\)
\(=-4x^2-37x-58\)
d) \(\left(x-3\right)^3+\left(x-5\right)\left(x^2+5x+25\right)-\left(x-1\right)\left(x^2+x+1\right)\)
\(=x^3-9x^2+27x-27+\left(x^3-125\right)-\left(x^3-1\right)\)
\(=x^3-9x^2+27x-151\)
e) \(\left(x-1\right)^3-\left(x-2\right)\left(x^2-2x+4\right)+3x^2+2x\)
\(=x^3-3x^2+3x-1-\left(x^3-8\right)+3x^2+2x\)
\(=5x+7\)
Nhẩm ấy, ko nháp âu
\(2x\left(x-7\right)-\left(x+3\right)\left(x-2\right)-\left(x+4\right)\left(x-4\right)\)
\(=2x^2-14x-\left(x^2-2x+3x-6\right)-\left(x^2-4x+4x-16\right)\)
\(=2x^2-14x-x^2+x-6-x^2+16\)
\(=-13x-10\)
\(2x\left(x+1\right)^2-\left(x-1\right)^3-\left(x-2\right)\left(x^2+2x+4\right)\)
\(=2x\left(x^2+2x+1\right)-\left(x^3-3x^2+3x-1\right)-\left(x-2\right)\left(x+2\right)\)
\(-2x^3+4x^2+2x-x^3+3x^2-3x+1-x^2+4\)
\(=-3x^3+6x^2-x+5\)
\(\text{a) 7-2x=22-9x}\)
\(\Leftrightarrow\text{7-2x-22+9x=0}\)
\(\Leftrightarrow-15+7x=0\)
\(\Leftrightarrow7x=15\)
\(\Leftrightarrow x=\frac{15}{7}\)
Học tốt
#Thảo Vy#
a)(ab−1)2+(a+b)2
=a2b2−2ab+1+a2+2ab+b2
=a2b2+1+a2+b2=a2(b2+1)+(b2+1) = (a2+1)(b2+1)
c)x3−4x2+12x−27
=x3−27+(−4x2+12x)
=(x−3)(x2+3x+9)−4x(x−3)
=(x−3)(x2+3x+9−4x)
=(x−3)(x2−x+9)
b)x3+2x2+2x+1
=x3+2x2+x+x+1
=x(x2+2x+1)+(x+1)
=x(x+1)2+(x+1)
=(x+1)(x(x+1)+1)
=(x+1)(x2+x+1)
d)x4−2x3+2x−1
=x4−2x3+x2−x2+2x−1
=x2(x2−2x+1)−(x2−2x+1)
=(x2−2x+1)(x2−1)
=(x−1)2(x−1)(x+1)
=(x−1)3(x+1)
e)x4+2x3+2x2+2x+1
=x4+2x3+x2+x2+2x+1
=x2(x2+2x+1)+(x2+2x+1)
=(x2+2x+1)(x2+1)
=(x+1)2(x2+1)
a) \(\left(2x+3\right)^2-3\left(x-4\right)\left(x+4\right)=\left(x-2\right)^2+1\)
\(\Leftrightarrow4x^2+12x+9-3\left(x^2-16\right)=x^2-4x+4+1\)
\(\Leftrightarrow4x^2+12x+9-3x^2+48=x^2-4x+5\)
\(\Leftrightarrow x^2+12x+57=x^2-4x+5\)
\(\Leftrightarrow16x+52=0\)
\(\Leftrightarrow x=-\frac{13}{4}\)
b) \(\left(3x-2\right)\left(9x^2+6x+4\right)-\left(3x-1\right)\left(9x^2-3x+1\right)=x-4\)
\(\Leftrightarrow\)Xem lại đề !
c) \(x\left(x-1\right)-\left(x-3\right)\left(x+4\right)=5x\)
\(\Leftrightarrow x^2-x-x^2-x+12=5x\)
\(\Leftrightarrow-2x+12=5x\)
\(\Leftrightarrow7x-12=0\)
\(\Leftrightarrow x=\frac{12}{7}\)
d) \(\left(2x+1\right)\left(2x-1\right)=4x\left(x-7\right)-3x\)
\(\Leftrightarrow4x^2-1=4x^2-28x-3x\)
\(\Leftrightarrow28x+3x-1=0\)
\(\Leftrightarrow31x-1=0\)
\(\Leftrightarrow x=\frac{1}{31}\)
4 + 2x(2x+4)=-x
<=>4 + 4x+8=-x
<=>12=-5x
<=>x=-2,4
k mình nhé